Technology Acceptance Model Perilaku Pengguna pada Sistem Enterprise Dompet Dhuafa - Imam Ali Khumaidi; Rinda Hesti Kusumaningtyas (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2021)
Dompet Dhuafa Enterprise System (DESI) is a system created in 2015. Initially it was created to replace the Fundrising Administration System (SANDRA) because SANDRA is a desktop-based application. Nowadays DESI is only used for budgeting functions and “Tebar Hewan Kurban” (THK) its a sacrificial animal stocking functions. DESI which has daily functions such as budgeting and seasonal functions in THK. In its implementation, DESI which is a web-based system sometimes becomes difficult to access when the system has a problem. This certainly makes the budgeting function that is used in daily activities become not implemented. THK's function in DESI was also inseparable from problems, one of which was the presence of volunteers who did not directly enter the data of prospective victims into DESI during the THK implementation. New data entered into DESI on the first Tasyrik day, for example, will increase work in other divisions. It would be different if it had been done before the sacrificial feast. This study aims to determine the factors that influence the acceptance behavior of DESI users. In this quantitative study using the Technology Acceptance Model (TAM) model. Sampling in this study using purposive sampling and accidental sampling. This study uses PLS-SEM for data processing and uses the application of SmartPLS version 3. There are 6 variables examined in this study, namely perceived usefulness, perceived easy of use, format, attitude using, behavioral intention to use, and actual system usage. From 7 hypotheses proposed there is one hypothesis that is rejected, namely the path attitude toward using the behavioral intention to use.